DAMD and ISSR DNA molecular analyses of regenerated cryopreserved Dendrobium Sabin Blue’s protocorm-like bodies (PLBS) - Jessica Jeyanthi James Antony,; Suhana Zakaria,; Safiah Ahmad Mubarakh,; Rahmad Zakaria,; Eldred Embu,; Sreeramanan Subramaniam, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The Orchidaceae is known as one of the most species-rich families of the plant kingdom. Orchids are generally declining in their natural habitat due to habitat loss and overharvesting for ornamental and medicinal purposes. Dendrobium Sabin Blue is widely grown as a cut flower and pot plant and is also popular for its deep violet-blue flowers. Developing these new orchid hybrids is tedious work; it is important to preserve them. Tissue culture and cryopreservation of plants can be employed to produce plantlets on an industrial scale. However, it may lead to genetic instability due to somaclonal variation. This study is to assess the genetic stability of regenerated cryopreserved and non-cryopreserved PLBs in comparison to stock culture PLBs using directed amplification of minisatellite DNA regions (DAMD) and inter-simple sequence repeat (ISSR) DNA molecular analyses. In general, regenerated explants should be identical to the mother plant. Seventeen (17) DAMD primers and twenty (20) ISSR primers were used to assess genetic stability between the 4-week-old cryopreserved/non-cryopreserved PLBs and the PLBs of the parent culture. Finally, DAMD and ISSR analyses confirmed the occurrence of 7% polymorphism and monomorphism, respectively, in the regenerated cryopreserved PLBs. Future studies should include further evaluation of somaclonal variations for long-term maintenance of cryopreserved PLBs.